Personal mental health navigator: Harnessing the power of data, personal models, and health cybernetics to promote psychological well-being - Rahmani, Amir M.; Lai, Jocelyn; Jafarlou, Salar; Azimi, Iman; Yunusova, Asal; Rivera, Alex. P.; Labbaf, Sina; Anzanpour, Arman; Dutt, Nikil; Jain, Ramesh; Borelli, Jessica L. (Frontiers in Digital Health, 2022)
Current digital mental healthcare solutions conventionally take on a reactive approach, requiring individuals to self-monitor and document existing symptoms. These solutions are unable to provide comprehensive, wrap-around, customized treatments that capture an individual’s holistic mental health model as it unfolds over time. Recognizing that each individual requires personally tailored mental health treatment, we introduce the notion of Personalized Mental Health Navigation (MHN): a cybernetic goal-based system that deploys a continuous loop of monitoring, estimation, and guidance to steer the individual towards mental flourishing. We present the core components of MHN that are premised on the importance of addressing an individual’s personal mental health state. Moreover, we provide an overview of the existing physical health navigation systems and highlight the requirements and challenges of deploying the navigational approach to the mental health domain.